PENATAAN ARSIP IMB (IZIN MENDIRIKAN BANGUNAN) DI BADAN PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI DKI JAKARTA - , AGISTA QURHAENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report with theme is the arraggement of IMB in BPAD Provinsi DKI Jakarta, gives details about practice of arrangement of IMB conducted during PKL. The implementation arragement of IMB start from transfering IMB records from creating agency to BPAD as Archival Institution, clasification of the IMB records, making of the inventarisation of records list, gives labeling at records box, shelfing, and retrieval. There are three methods using in practice. The first method is observation and practice. Observation and participating the process aranggement of IMB records. The second method is literature study which applied to collect data from books or other texts related with the arrangement of IMB records. The last method is interview with proposing many questions about the arrangement of IMB to Subbidang Pengolahan. The result of PKL at Badan Perpustakaan dan Arsip Daerah Provinsi DKI Jakarta show that record management is well done. This is showed start from the arragement records well whish is easier in the retrieval. After all, it still lacks of human resources to arrange IMB records.